The Linguistic Construction of Meaning in Niki’s “La La Lost You” through Halliday’s Systemic Functional Linguistics - Ayu Maulidina; Julia Crist Ei Riyanti; Rihadatul Aisy; Dhea Amelia Artikasari (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2026)
This study explores the linguistic construction of meaning in NIKI’s song “La La Lost You” by applying Halliday’s Systemic Functional Linguistics (SFL) theory, particularly focusing on the three metafunctions: ideational, interpersonal, and textual. As a lyrical text that expresses loss, longing, and emotional vulnerability, “La La Lost You” offers rich data for analyzing how language conveys both personal emotion and social meaning. The purpose of this research is to identify how NIKI’s linguistic choices represent experiences, establish emotional relationships with the listener, and organize ideas cohesively through the metafunctional framework. This study employs a qualitative descriptive approach, using textual analysis of the song lyrics to examine transitivity structures, mood and modality patterns, and thematic organization. The findings reveal that mental and relational processes dominate the ideational metafunction, emphasizing the singer’s inner feelings and perceptions. The interpersonal metafunction highlights the use of declarative moods and personal pronouns, which create an intimate and confessional tone between the singer and the audience. The textual metafunction demonstrates cohesive thematic progression, contributing to the emotional flow of the lyrics. Overall, this study illustrates how the three metafunctions interact to construct emotional depth and coherence, revealing the linguistic strategies through which NIKI communicates personal loss and emotional resonance in “La La Lost You”.